Sediment core description of gravity core GeoB23163-1 recovered during R/V Poseidon expedition POS499 at Sartori MV in the Calabrian Arc, Mediterranean Sea - Mechthild Doll; Markus Loher; Gerhard Bohrmann (PANGAEA, 2023)
During R/V Poseidon expedition POS499, sediment core GeoB23163-1 (GC21) was collected with a gravity corer at the top of the Sartori Mud Volcano located in the Calabrian accretionary prism (Mediterranean Sea). The gravity core was recovered in a plastic foil, photographed and described on board. The gravity core is not stored in any core repository. To investigate lithological changes in more detail, macroscopic core description is prepared. The core description provides information about core length, position, water depth, core sections, core image, color, lithology, sedimentary structures and a descriptive text. Sediment color was determined qualitatively using Munsell soil color charts.